Intra-Articular Injections of Allogeneic Mesenchymal Stromal Cells vs. High Molecular Weight Hyaluronic Acid in Dogs With Osteoarthritis: Exploratory Data From a Double-Blind, Randomized, Prospective Clinical Trial - Kim, Sohyun; Elam, Lindsay; Johnson, Valerie; Hess, Ann; Webb, Tracy; Dow, Steven; Duerr, Felix (Frontiers in Veterinary Science, 2022)
This double-blind, randomized, prospective clinical trial was conducted to obtain exploratory data comparing the efficacy of intra-articular allogeneic mesenchymal stem/stromal cells (MSC) to high molecular weight hyaluronic acid (HA) for the treatment of pain associated with canine osteoarthritis (OA). Objective gait analysis (%Body Weight Distribution, %BWD), accelerometry, clinical metrology instruments and veterinary exams were used as outcome measures during various time points throughout the 48-week study period. Fourteen dogs with elbow or coxofemoral OA were enrolled and assigned in a 2:1 ratio to the treatment groups. Each patient received a set of two injections 4 weeks apart. Self-limiting joint flare was observed in seven patients, with six of these in the MSC group. Ten patients completed all follow-up appointments. Both treatment groups showed evidence of mild improvement following the treatment, but the results were inconsistent among the various outcome measures assessed. Overall, dogs enrolled in the HA group showed greater improvement compared to the MSC group. The primary outcome measure, %BWD, showed evidence of improvement, when compared to baseline values, at 36 weeks after injection for the HA group only (p = 0.048, estimated difference: 4.7). Similarly, when treatment groups were compared, evidence of a difference between treatment groups (with the HA-group showing greater improvement) were identified for weeks 24 and 36 (p = 0.02 and 0.01, respectively). The small sample size of this exploratory study does not allow firm conclusions. However, until studies with larger sample sizes are available, the current literature combined with our data do not support the clinical use of intra-articular MSC therapy over high molecular weight HA for the treatment of canine OA at this time.